Effectiveness of educational interventions conducted in Latin America for the prevention of overweight and obesity in scholar children from 6-17 years old; a systematic review (2015)
Introduction: Overweight and obesity are serious public health problem, which is specially among children populations. Objective: To determine the effectiveness of educational interventions conducted in Latino America for the prevention of overweight and obesity in scholar children from 6 to 17 years old. Metodology: MEDLINE, LILACS and EMBASE were searched between february and may 2014 to retrieve randomized controlled trials and longitudinal studies that evaluated the effects of educational interventions intended to retrieve randomized controlled trials and longitudinal studies aiming to prevent overweight and obesity among Latinoamerican children. Risk of bias was evaluated using the PEDro scale and the CASPe tool. Results: Twenty one studies were included (n=12,092). Different types of educational interventions were identified, such as nutritional campaigns, physical activity practice and environmental changes. Mixed approaches combining nutritional campaigns, physical activity promotion and enviromental changes were the most effective interventions, since their results produced the largest improvements in the overweight and obesity of children. None evidence of reporting bias was observed. Conclusion: Educational interventions performed in the educational environment that combined an adequate nutrition and the promotion of physical activity practice, are more effective for preventing overweight and obesity in Latino American children, although familiar interventions are also encouraged approach, associated with better responses on the behavioral change in scholar children. © 2015, Grupo Aula Medica S.A. All rights reserved.